Penerapan Pengelolaan Tanah Wakaf Di Kelurahan Tamarunang Kecamatan Somba Opu Kota Makassar - Trisno Wardy Putra; Resti (CENDEKIA: Jurnal Studi Keislaman, 2021)
Indonesia is a country known as the country with the largest Muslim population in the world. However, the number of Indonesian people who already know and understand about waqf is still very small. Waqf problems in ex. Tamarunang, Kec. Somba Opu, Kab. Gowa is still only limited to the potential of waqf and has not fully shown its benefits. Problems arising from several waqf practices in the community are not only around the implementation of the waqf, but also in terms of the management and development of the waqf land. The purpose of this study was to determine the application of waqf land management. This research uses quantitative research methods. The data collection technique was carried out through observation and interviews, by taking a random sample (purposive sampling). The results of this study are from the total waqf land, it can be concluded that there are 128 waqf assets with an area (ha) of 6.71, 1 of which have been certified, while those who have not been certified are 127 with an area (ha) of 6.68.